SÍNTESE DE PORTLANDITA A PARTIR DE FERTILIZANTE E AMIDO APLICADA NA REMOÇÃO DE VERMELHO CONGO E REUSO COMO PIGMENTO HÍBRIDO - SILVA, DAIANE LOPES DA (2023)
In this study was developed from the synthesis of calcium oxide-hydroxide [CaO(OH)] using starch extracted from cassava as an alternative fuel source to reduce burning temperature and maintain the caustic and porous property of [CaO(OH) ]. The calcium source precursors used were commercial calcium nitrate (Fe-Com) and calcium agricultural fertilizer (Ca-Fer). The choice of calcium source precursors impose a cost difference, commercial nitrate is about 6 times the value of a kilogram of agricultural fertilizer. Both compounds were characterized by X-ray diffraction (DRX), Fourier transform infrared (FTIR), zeta potential () and energy dispersive spectroscopy (EDS). The VC dye removal tests were carried out in aqueous solutions containing 550-1050 mg.L-1 at temperatures of 25, 35 and 45 °C, the experimental data at equilibrium were adjusted according to the isotherms of Freundlich, Langmuir and Temkin.The diffractograms of the compounds identified the same phases in both samples, Portlandite (Ca(OH)2) and Lime (CaO), which are commonly found in calcium compounds. The zeta potential data resulted in the information that the samples have positive surface charge, being compatible as anionic species, and thus, were used in the removal of Congo red dye (VC). According to the Langmuir model, the maximum adsorption capacity (qmax) as a function of temperature was 265.2 (25 °C), 236.4 (35 °C) and 234.1 mg.g-1 (45 °C) ; increasing the temperature experienced the removal capacity for Ca-Fer sample. After the dye removal step, the artificially colored solids were reused as hybrid pigments, applied in commercial white paint and comparatively evaluated by colorimetry measurements in the CIEL*a*b* system. Color stability has been tested in acidic and alkaline environments. The samples proved to be efficient in discoloring VC and its reuse as a hybrid pigment.